A REVIEW: BEHAVIOR OF PITTING CORROSION IN MANUFACTURING FOOD EQUIPMENT - & et al., Alwan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
Corrosion is the deterioration or destruction of metals and alloys in the presence of an environment by chemical or electrochemical means. The phenomenon of corrosion behavior studies is three elements include economic, safety and maintenance. Pitting corrosion is a localized form of corrosion by which cavities or "holes" are produced interring the material layer surface. It's considered to be more dangerous than uniform corrosion damage because it is more difficult to detect, predict and design against. Pitting corrosion can produce pits with open holes or covered with a semi-permeable capsule of corrosion products. In this review, we study about the pitting corrosion mechanism and stages in the manufacture food equipment metals in different conditions and environment.